THE MEANING OF BIBIT, BEBET, BOBOT IN THE SELECTION OF PARTNERS : A STUDY OF PARENTS AND CHILDREN IN JAVA: Pemaknaan Bibit, Bebet, Bobot dalam Pemilihan Pasangan : Studi Pada Orang Tua dan Anak di Jawa - Tiberia Harsilo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The concept of bibit, bebet, and bobot represents a traditional cultural framework used by Javanese families in selecting potential life partners. Despite social and cultural transformations in modern society, this value system continues to influence parental perspectives and family decision-making. This study aims to explore the meaning of bibit, bebet, and bobot in partner selection as interpreted by parents and children, and to understand how these values are communicated within the family context. Using a qualitative phenomenological approach, data were collected through semi-structured focused group discussions involving a pair of parents and one adult child of Javanese ethnicity in Surabaya, as well as netnographic analysis of TikTok videos and public comments discussing the relevance of bibit, bebet, and bobot. The findings indicate that these values remain significant as moral, social, and cultural considerations in choosing a partner. Parents tend to emphasize traditional interpretations related to family background, economic stability, and moral character, while the younger generation interprets these values more flexibly in accordance with contemporary contexts. Communication through storytelling and personal narratives plays a crucial role in transmitting and negotiating these values across generations. This study concludes that bibit, bebet, and bobot remain relevant in modern society when communicated openly and adaptively, allowing negotiation between tradition and present-day relational needs.